The Influence of Institutional Ownership and Debt Policy on Dividend Policy and Profitability as a Moderation Variable - Puspita, Sella (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This research aims to examine the influence of institutional ownership and debt policy on dividend policy with profitability as a moderating variable (in IDX30 index companies listed on the Indonesian stock exchange in 2019-2021). The research method used in this research is quantitative research and uses secondary data collection techniques in the form of annual reports. The sample in this study was selected using a purposive sampling method and a sample of 16 IDX30 companies was obtained that met the sample criteria. The data analysis method used is multiple linear regression analysis and moderated regression analysis. The results of this research indicate that institutional ownership and debt policy have no effect on dividend policy. Moderating profitability can weaken the influence of institutional ownership on dividend policy. And profitability can strengthen the influence of debt policy on dividend policy.